Sex dimorphism in isoproterenol-induced cardiac damage associated neuroinflammation and behavior in old rats - Tóth, Kata; Oroszi, Tamás; van der Zee, Eddy A.; Nyakas, Csaba; Schoemaker, Regien G. (Frontiers in Aging Neuroscience, 2022)
Acute cardiac damage can be induced by isoproterenol injections in animals. The associated inflammatory response could be reflected in the brain as neuroinflammation, with potential consequences for brain function and behavior. Although cardiac responses are reported age and sex-related, for neuroinflammation and brain function this is virtually unknown. Therefore, cardiac damage and its consequences for neuroinflammation, brain function and behavior were compared in aged male and female rats. Wistar rats of 24 months of age were treated with isoproterenol (ISO, twice s.c.) or saline. Four weeks after injections, exploratory behavior and short-term memory were tested. Then, rats were sacrificed. Hearts were collected to measure cardiac damage. Brain tissue was collected to obtain measures of neuroinflammation and brain function. In male-, but not in female rats, ISO induced significant cardiac damage. Accordingly, mortality was higher in males than in females. Baseline hippocampal microglia activity was lower in females, while ISO induced neuroinflammation in both sexes, Hippocampal brain-derived neurotrophic factor expression appeared lower in females, without effects of ISO. In the open field test, ISO-treated males, but not females, displayed anxiety-like behavior. No effects of ISO were observed on short-term memory in either sex. In conclusion, sex dimorphism in effects of ISO was observed for cardiac damage and open field behavior. However, these effects could not be related to differences in hippocampal neuroinflammation or neuronal function.